Plasmid‐mediated resistance to cephalosporins and quinolones in Escherichia coli from American crows in the USA. (12th April 2017) - Jamborova, Ivana; Dolejska, Monika; Zurek, Ludek; Townsend, Andrea K.; Clark, Anne B.; Ellis, Julie C.; Papousek, Ivo; Cizek, Alois; Literak, Ivan
Summary: American crow ( Corvus brachyrhynchos ) faeces were tested for Escherichia coli with plasmid‐mediated quinolone resistance (PMQR), extended‐spectrum beta‐lactamases (ESBL) and AmpC beta‐lactamases. A total of 590 faecal samples were collected at four roosting sites in the USA and cultivated on selective media. Pulsed‐field gel electrophoresis (PFGE) and multi‐locus sequence typing (MLST) were performed to assess clonality. Transferability of resistance genes was studied using conjugation and transformation bioassays. In total, 78 (13%, n  = 590) cefotaxime‐resistant isolates were obtained, of which 66 and 12 displayed AmpC and ESBL phenotypes, respectively. Fifty‐four AmpC‐producing isolates carried bla CMY‐2 . Isolates producing ESBLs contained genes bla CTX‐M‐27 (5 isolates), bla CTX‐M‐15 (4), bla CTX‐M‐14 (2) and bla CTX‐M‐1 (1). Ninety isolates (15%, n  = 590) with reduced susceptibility to ciprofloxacin were obtained, among which 14 harboured PMQR genes aac(6′)‐Ib‐cr (4 isolates), qnrB19 (3), qnrS1 (2), qnrA1 (2), qnrB2 (1), qnrB6 (1) and qnrD3 (1). High genetic diversity was revealed by PFGE and MLST. Epidemiologically important E. coli clones (e.g., ST131, ST405) were identified. Plasmids carrying bla CMY‐2 were assigned predominantly to IncA/C (8 plasmids), IncI1/ST23 (5) and IncI1/ST12 (3). The study demonstrates a widespread occurrence of E. coli with ESBL, AmpC and PMQR genes associated with clinically important multidrug‐resistant clones and epidemic plasmids, in American crows.